Integration of the Concept of Manners in Classroom Management at Sinar Husni Private Junior High School - Marsyeli , Marsyeli; Rustam , Rustam (FKIP - Universitas Riau, 2025)
The decline of manners in the educational environment, such as students' low respect for teachers and lack of discipline, is a fundamental problem that demands strategic solutions. This study aims to describe the integration of adab values in classroom management at Sinar Husni Private Junior High School to create a religious and character learning atmosphere. Using a descriptive qualitative approach with interview, observation, and documentation techniques, as well as data analysis of the Miles and Huberman model, this study reveals that the values of manners are systematically integrated in the aspects of planning, organizing, implementing, and evaluating classroom management. Values such as manners, greetings, respect for teachers, and worship habits are an important part of shaping student character. The role of teachers as role models and facilitators determines the success of the application of these values. The results show that adab-based classroom management is able to create a conducive, moral and spiritual learning atmosphere. Therefore, it is recommended that Islamic-based schools adopt this approach and equip teachers with moral leadership training in order to form a generation that is not only intellectually intelligent, but also morally and spiritually superior.